2018
DOI: 10.5194/acp-18-8529-2018
|View full text |Cite
|
Sign up to set email alerts
|

Detection and variability of combustion-derived vapor in an urban basin

Abstract: Abstract. Water emitted during combustion may comprise a significant portion of ambient humidity ( > 10 %) in urban areas, where combustion emissions are strongly focused in space and time. Stable water vapor isotopes can be used to apportion measured humidity values between atmospherically transported and combustion-derived water vapor, as combustion-derived vapor possesses an unusually negative deuterium excess value (d-excess, d = δ 2 H − 8δ 18 O). We investigated the relationship between the d-excess of at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 69 publications
3
39
0
Order By: Relevance
“…The Uintah Basin GHG network has supported several recent projects including Foster et al (2017Foster et al ( , 2019, in which the data collected from this network were used to estimate and confirm basin-wide CH 4 emissions and examine CH 4 emissions during wintertime stagnation episodes respectively. In an effort to minimize differences between the two networks, measurement frequency, networking, calibration materials (Sect.…”
Section: Uintah Basin Ghg Network Instrumentationmentioning
confidence: 99%
“…The Uintah Basin GHG network has supported several recent projects including Foster et al (2017Foster et al ( , 2019, in which the data collected from this network were used to estimate and confirm basin-wide CH 4 emissions and examine CH 4 emissions during wintertime stagnation episodes respectively. In an effort to minimize differences between the two networks, measurement frequency, networking, calibration materials (Sect.…”
Section: Uintah Basin Ghg Network Instrumentationmentioning
confidence: 99%
“…We used Version 1.2 of the University of Utah vapor processing scripts (Fiorella, Bares, et al, 2018) to cali-brate~1-Hz isotope data and determine instrument precision. We found that isotope values varied with humidity.…”
Section: Water Vapor Isotope Measurementsmentioning
confidence: 99%
“…Our measurements of isotopes in water vapor (Figure 3a) trace a local atmospheric water line with a slightly shallower slope (6.8) and a smaller intercept (−5.9%) relative to the GMWL. Potential contributors to these differences include wind speeds during evaporation from the nearby sea surface, isotopic distillation during transport, partial evaporation of raindrops during rainfall, and the ratio of transpiration to evaporation in the local ecosystem, among others [26][27][28][29][30]. Figure 3b further shows that the value of d-excess is inversely related with δ 18 O.…”
Section: Local Conditionsmentioning
confidence: 92%
“…is insensitive to (reversible) equilibrium fractionation, and is therefore often used to infer the location or meteorological conditions that characterize the vapor source region under the assumptions that kinetic effects and water loss during transport are small [24,25]. Several recent studies have suggested that the interpretation of d-excess is less straightforward than originally thought [26][27][28][29]; however, as a general rule, values of d-excess are positively correlated with temperature and negatively correlated with RH at the evaporative source. These signals may be confounded by other factors, such as strong winds at the evaporative source or the partial evaporation of falling rain [24,30].…”
Section: Stable Water Isotopesmentioning
confidence: 99%